Epidemiology, aetiology and screening of bladder cancer - Cumberbatch, Marcus G. K. (Transl Androl Urol, 2019)
Bladder cancer (BC) is a common, significant and expensive health condition. Understanding the risk factors for this disease is paramount to improving disease prevention and increasing public awareness. Historically BC has been a disease of industrialized regions and the most responsible carcinogens are tobacco smoke and occupational chemical exposure. BC incidence and mortality differ dramatically by region and reflect differences in risk factor exposure, healthcare behaviour, and population demographics. Screening studies have suggested a survival benefit amongst screened non-symptomatic populations with known risk factors, but this has not become standard practice.